Warkany Syndrome: A Rare Case Report - Amit Agrawal; Rashmi Agrawal (Case Reports in Pediatrics)
Warkany syndrome 2 or Trisomy 8 mosaicism (T8M) is a well-described, but very rare, chromosomal abnormality. The phenotype is extremely variable ranging from normal individual to severe malformation syndrome and because of this variability, this condition often goes undiagnosed. We report trisomy 8 mosaicism (T8M) in a 3-year-old boy evaluated for facial dysmorphism and delayed development.